Strategi Pertahanan Indonesia Melalui Pembangunan Pos Lintas Batas Negara (PBLN) Entikong dalam Perspektif Geostrategi - Tia Angelina,; Simanjuntak, Triesanto Romulo; Hadiwijoyo, Suryo Sakti (Jurnal Social Science, 2024)
This research aims to examine Indonesia's defense strategy implemented through the construction of the Entikong National Border Post (PLBN), focusing on analysis from a geostrategy perspective. The research method used in this research is a qualitative analysis method, with data collection through literature study and analysis of official documents as well as interviews with the Head of the Entikong PLBN Management Division. This approach provides a comprehensive perspective on Indonesia's defense strategy in border areas. The research results show that the construction of the Cross-Border Post in Entikong is in line with Indonesia's national defense strategy which focuses on regional cooperation and resource management in border areas. In a geostrategic perspective, this research also highlights the importance of Entikong's geographical position as a strategic point that influences national defense. The defense strategy implemented through the Entikong Cross Border Post reflects adaptation to geopolitical dynamics in the region. This research contributes to further understanding of the implementation of Indonesia's defense strategy in a geostrategy context and can be a basis for the government and stakeholders to develop and improve national defense strategies in the future, especially in facing the changing geopolitical dynamics in this region